The role of gestures in a teacher–student-discourse about atoms. Issue 3 (16th June 2016) - Abels, Simone
Abstract : Recent educational research emphasises the importance of analysing talk and gestures to come to an understanding about students' conceptual learning. Gestures are perceived as complex hand movements being equivalent to other language modes. They can convey experienceable as well as abstract concepts. As well as technical language, gestures referring to chemical concepts can be a challenge for students and cause misunderstandings. The study presented here focuses on a chemistry teacher's use of gestures in a discourse about atoms. The questions of interest are how the teacher uses certain gestures, if her intentions can be reconstructed and if students seem to understand the content-related gestures. Analysis is done by applying the steps of the Documentary Method. The results show that the teacher uses imagistic gestures, because of the assumption that students can remember and understand the abstract concepts of chemistry faster by using scaffolding in forms of visualisation. Challenges of using gestures to visualise abstract chemistry concepts are discussed.